Impact of surface acting and deep acting techniques on teachers' organizational commitment. Issue 1 (12th February 2020) - Ogunsola, Kazeem Olanrewaju; Fontaine, Rodrique Ancelot Harvey; Jan, Muhammad Tahir
Abstract : Purpose: This paper aims to examine the relationship between surface acting (SA), deep acting (DA) and organizational commitment (OC). Design/methodology/approach: Guided by affective events theory, the study adapted emotional labour scale and three components model to profile 373 teachers from 30 schools around Peninsular Malaysia. A list-based simple random sampling technique was used to select respondents. Structural equation modeling (SEM) was used to test hypotheses, and the proposed model was assessed through renowned fit indices. Findings: OC was hypothesized as a second-order construct. SEM result indicates that both SA and DA have significant negative relationship with OC. Fit indices of the hypothesized model showed χ²/ df ratio (560.069/265) = 2.113, RMSEA (0.055), and CFI (0.936). This result provides empirical support for the data collected. Research limitations/implications: The study provides new insight on the ongoing debate about SA and DA. Therefore, it advances body of research in this regard. The implication for HR managers is that strategic polices can be institutionalized to buffer the consequences of SA and DA. This is due to the fact that SA and DA may not be abolished for service employees like teachers. The practical implication for teachers is the understanding that emotional regulation process is inevitable because teaching is profoundly an emotional activity job. Besides being a cross-sectional study, the sampled population may have limited the study's outcomes. Originality/value: Given existing inconsistent results on the consequences of SA and DA, this study shows that not only SA can lead to negative after-effects, DA can also cause the same. Future study can explore spiritual intelligence to examine how best SA and DA can be performed at reduced consequences on OC.